Post-cholecystectomy Syndrome Due To Stump-Stones: A Possibility (Journal of Chittagong Medical College Teachers' Association, 2014)
Recurrence of biliary symptoms following cholecystectomy either laparotomic or laparoscopic, is quite common. Causes are either biliary or extra-biliary. Symptoms of biliary origin chiefly depends on residual stones, biliary stricture, rarely depends on stones in cystic duct or gallbladder remnant. Diagnosis of stump-stones is difficult, mainly arising from USG, MRCP,CT-scan, ERCP. Completion cholecystectomy can be done by laparotomy or laparoscopically. We report two cases of stump-stones discovered after 10 years & 5 years following lap chole and minilap cholecystectomy respectively, who were diagnosed by USG, CT-scan and managed by open completion cholecystectomy. Stump-stones can be a possibility of post cholecystectomy syndrome even after 10 years and surgeons should be aware of it.JCMCTA 2014 ; 25 (2) : 49-53